2018
DOI: 10.1039/c8qm00314a
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in macrocyclic amphiphiles and macrocyclic host-based supra-amphiphiles

Abstract: In this review, recent progress in macrocyclic amphiphiles and macrocyclic host-based supra-amphiphiles is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 332 publications
0
57
0
Order By: Relevance
“…In addition, formation of aggregates via self assembly, charged species and changes in opto-electronic properties, employed in actuators, sensors and piezoelectrics ( Figure 19). [77][78][79] Steinberg et al, reported synthesis of Schiff bases appended benzimidazole moiety with alternating imino nitrogen containing À CN/NO 2 for protonation act as optodes in sensing metal and fluoride ions in solutions. The acid-base titration for À NO 2 linked Schiff base results color transition from yellow to orange in ethanol/water mixtures.…”
Section: Chemical and Heat Responsive Smart Materials: Applications Fmentioning
confidence: 99%
“…In addition, formation of aggregates via self assembly, charged species and changes in opto-electronic properties, employed in actuators, sensors and piezoelectrics ( Figure 19). [77][78][79] Steinberg et al, reported synthesis of Schiff bases appended benzimidazole moiety with alternating imino nitrogen containing À CN/NO 2 for protonation act as optodes in sensing metal and fluoride ions in solutions. The acid-base titration for À NO 2 linked Schiff base results color transition from yellow to orange in ethanol/water mixtures.…”
Section: Chemical and Heat Responsive Smart Materials: Applications Fmentioning
confidence: 99%
“…Owing to their amphiphilic nature, amphiphiles can self-assemble into various nanostructures in water that can be applied in various areas, including drug/gene delivery, photodynamic therapy, and bioimaging (Zhang and Wang, 2011;Hu et al, 2013;Kelley et al, 2013;Ma and Zhao, 2015;Yu et al, 2015;Ji et al, 2016;Xia et al, 2016;Webber and Langer, 2017;Guo et al, 2018;Zuo et al, 2018;Wang S.-P. et al, 2019;. Amphiphiles synthesized based on macrocyclic compounds, namely, macrocyclic amphiphiles (Jie et al, 2015;Zhu et al, 2018), have gained growing attention in recent years. Compared with traditional amphiphiles, macrocyclic amphiphiles possess unique superiority in the construction of various functional nanomaterials, e.g., the incorporation of functional groups and intriguing properties can be achieved by host-guest interactions without extra additives and tedious synthesis (Wei et al, 2014;Wang et al, 2015;Shulov et al, 2016;Geng et al, 2017;Redondo-Gomez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Inclusion complex formation is a versatile tool in supramolecular chemotherapy and in the creation of tailor-made functional nanostructures. 3,4 The capability of synthetic host compounds to recognize amino acids, peptides, and protein surface elements can be used to modulate the interactions between proteins and to modify the activity of biomolecules. 5,6 Among water-soluble biocompatible hosts, cucurbiturils (CBn) and their acyclic analogues have attracted particular attention due to their remarkable binding capability.…”
Section: Introductionmentioning
confidence: 99%